Administration for the Intellectual Property Protection of Rajamangala University of Technology - Khamput, Prachoom; Polpak, Dr.Sampan (Journal for Developing the Social and Community, 2018)
The purposes of this research were to study; 1) problems of administration, 2) development guidelines of administration, and 3) important factors effecting to development guideline success of administration for the success intellectual property protection of Rajamangala University of Technology. The questionnaire was used as a tool to collect the data. The population consisted of academic staffs and 9 faculty members of the Rajamangala University of Technology. The 874 samples were selected and the 607 questionnaires were collected from all samples. The descriptive analysis was used to analyze data including : frequency, percentage, mean, and standard deviation. In terms of qualitative research, the deep interviews were applied to support the quantitative research. From the results, showed that (1) The Rajamangala University of Technology had the problems of intellectual property protection in moderate level and they should develop the administration in moderate level too. (2) The significant administration problem was the intellectual property protection encouragement of Rajamangala University of Technology was not enough. (3) The contribute significantly to the administration development approach was the Rajamangala University of Technology should encourage the staffs to pay attention about the protection of intellectual property as much as possible. Moreover, the effective administration development approach to improve the administrators of Rajamangala University of Technology was the good vision and clear policy of board about the intellectual property protection. And the implement of modern technology also facilitate and enhance the administration.